Implementation of a virtual classroom in Moodle for learning mathematics within the framework of relational education (Revista Innova Educación, 2022)
The departmental school Pio XII, located in Colombia, is one of the educational centers that implemented the relational education system. Thanks to this process, shortcomings were evidenced in the personalized attention offered by teachers. In this sense, the present research aims to establish the incidence of implementing a virtual classroom designed in Moodle for the learning of mathematics under the considerations of the relational system with the seventh-grade students of this institution. It was carried out with a quantitative approach, based on a correlational cross-sectional design, where seven previously designed instruments were applied. The information of the three scenarios was collected: before, during, and after the implementation of the virtual classroom, which led to making comparisons of 46 different processes. The results reveal that the virtual classroom makes the analyst's attention time more efficient since it allows the student to develop metacognitive skills that strengthen her autonomy process. In addition, as a consequence, it was shown that the virtual classroom generates a progressive increase in the students' academic results.
Keywords: learning; autonomy; skills; metacognition; Moodle